2018
DOI: 10.1242/jeb.185348
|View full text |Cite
|
Sign up to set email alerts
|

Should I stay or should I go? The settlement-inducing protein complex guides barnacle settlement decisions

Abstract: Reproduction in barnacles relies on chemical cues that guide their gregarious settlement. These cues have been pinned down to several sources of settlement pheromones, one of which is a protein termed settlement-inducing protein complex (SIPC), a large glycoprotein acting as a pheromone to induce larval settlement and as an adhesive in surface exploration by the cyprids. Settlement assays in laboratory conditions with Amphibalanus (=Balanus) amphitrite cyprids in the presence of SIPC showed that cyprids exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…Wells were then blocked by incubation with 5% BSA in TBST (25 mM Tris-HCl, pH 7.5, 150 mM NaCl, 0.1% Tween 20) for 1 h at room temperature. Wells were then incubated for 1 h at room temperature with the mouse anti-SIPC monoclonal antibody [28] at 1:100 dilution of the cloned cell line culture supernatant in TBST with 5% BSA, washed with TBST (3 × 5 min) and incubated with an HRP-conjugated anti-mouse antibody (1:1000, Cell Signaling Technology, Danvers, MA, USA) for 1 h at room temperature. Wells were then washed with TBST (3 × 5 min) and immunostaining was detected using the 20 × LumiGLO ® chemiluminescence kit (Cell Signaling Technology, Danvers, MA, USA) in a Bio-Rad ChemiDoc XRS + Gel Photo Documentation System.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wells were then blocked by incubation with 5% BSA in TBST (25 mM Tris-HCl, pH 7.5, 150 mM NaCl, 0.1% Tween 20) for 1 h at room temperature. Wells were then incubated for 1 h at room temperature with the mouse anti-SIPC monoclonal antibody [28] at 1:100 dilution of the cloned cell line culture supernatant in TBST with 5% BSA, washed with TBST (3 × 5 min) and incubated with an HRP-conjugated anti-mouse antibody (1:1000, Cell Signaling Technology, Danvers, MA, USA) for 1 h at room temperature. Wells were then washed with TBST (3 × 5 min) and immunostaining was detected using the 20 × LumiGLO ® chemiluminescence kit (Cell Signaling Technology, Danvers, MA, USA) in a Bio-Rad ChemiDoc XRS + Gel Photo Documentation System.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of surface exploration activity of A. amphitrite cyprids in the presence of perforenol ( 9 ) and bromosphaerol. ( A ) A mouse anti-SIPC monoclonal antibody that can detect native SIPC deposited by cyprids of A. amphitrite on the surface of polystyrene tissue culture plates [28] was used in Western blots after A. amphitrite settlement bioassays in the presence of perforenol ( 9 ) and bromosphaerol or artificial sea water (ASW, serving as control). Sterile tissue culture plates were incubated at 25 °C without (blank) or with 10 cyprids each in 2 mL sterile ASW for 24 h in the presence or absence (ASW) of the indicated concentrations of perforenol ( 9 ) or bromosphaerol.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This stimulates a clustered settlement, which increases the reproductive chances of the group. While low concentrations of SCIP stimulate settlement, higher concentrations have the opposite effect to avoid overpopulation of an area (Kotsiri et al, 2018).…”
Section: Chemical Cues By Other Organismsmentioning
confidence: 99%
“…While the exact mechanism remains unknown, it has been suggested that either variable regions of the SIPC or glycosylation patterns might provide species specificity (Yorisue et al 2012). Further research showed that SIPC has a dual role; it works as a settlement-inducing cue by attracting cyprids, but also as a settlement avoidance cue at higher concentrations informing of overcrowding and increased reproductive competition (Kotsiri et al 2018). A SIPC homologue has also been identified and characterised in Balanus glandula (called MULTIFUNCin) where it induces both gregariousness as well as predation by sea snails (Ferrier et al 2016;Zimmer et al 2016).…”
Section: Introductionmentioning
confidence: 99%